School Management System: Safety and Security(With Mobile Application and Web-Based Management System): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Office of Safety and Security has a lot of problems in preserving its data, particularly inmonitoring reports, certificates, and passes and inspecting infrastructures. The staff needs tosubmit a narrative report to the OIC and scan each paper carefully. It takes a lot of time, effortsand it affects the productivity of the department, especially the problem of pilling a requestitem; then OIC needs to go back and forth to submit and follow up on the progress of therequest to different campuses of the Bestlink College of the Philippines. In reality, speaking ittakes a lot of budget for the department’s operation cost.As a result, the developers successfully created a system that met all the client requirementsthat you can see in the project's deliverables and product backlog. As you can see, AppendixF shows how the client navigated the system and gave the system a 90% completion rate.They wanted the system to be implemented in their department. The system helps the Officeof Safety and Security monitor, report, make and release passes, and request items withoutgoing out into their workplace. Lastly, the safety officers can easily track and inspect thefacility by simply inputting information into the mobile application and web managementsystem.I have a deep understanding of the study and complied with all the requirements needed. Thedevelopers successfully implemented and migrated the data to the new system approach. Themodules and submodules are successfully working by inputting data into mobile applicationsthat will appear or see the output to the web-based system. Also, the web has an input featurelike mobile so that the personnel can navigate the system through the web.
Keywords: IT & Management